Preface : Land Surface Processes and Interactions—From HCMM to Sentinel Missions and Beyond - Vekerdy, Z. (2020)
Recognizing the importance to better understand these complex processes and interactions, the World Climate Research Programme (WCRP) launched the Global Energy and Water Cycle Experiment (GEWEX) in 1990, which has been currently evolved into Phase III as Global Energy and Water Exchanges (GEWEX), with its mission to measure and predict global and regional energy and water variations, trends, and extremes, via improved observations and modelling of land, atmosphere, and their interactions geography of the ICA.